IMPLEMENTASI AKAD MURABAHAH PADA PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) DI BANK SYARIAH INDONESIA - Deti Iryani; Dea Sri Utari; Mashuri Mashuri; Susilawati Susilawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Micro KUR financing is one of the financing options offered by Bank Syariah Indonesia to the public as customers to run micro or small and medium enterprises. The purpose of this research is to examine the implementation of the murabaha contract in the financing of People's Business Credit (KUR). The research was conducted from August to September 2024. During the author's professional internship (MP), the author was able to analyze the performance at BSI KCP Dumai Sukajadi, which was very good and in accordance with applicable regulations. The murabaha contract implemented is also in line with sharia principles. If the goods desired by the customer cannot be directly purchased by the bank, for example, the purchase of essential goods, the bank will use a wakalah contract, where the purchase of goods will be delegated to the customer with the condition that proof of purchase is submitted to the bank. The implementation of the murabaha contract is expected to run smoothly and as effectively as possible.